Novel Treatment of Laryngomalacia: A Case Series - Fatima, Tazeen; Hussain, Muhammad Amjad; Sajid, Muhammad; Arfan, Hadeeba; Awan, Amna; Arif, Maria (Journal of Health and Rehabilitation Research, 2024)
Background: Laryngomalacia is a prevalent neonatal condition characterized by the increased pliability of laryngeal tissues, leading to airway obstruction and associated respiratory complications. It necessitates a nuanced approach to diagnosis and management, given its variable clinical presentation and potential for significant morbidity. Objective: This study aims to investigate the clinical presentation, management, and outcomes of neonates with laryngomalacia, focusing on the efficacy of individualized treatment approaches including bronchoscopy, laser ablation, and various ventilation strategies. Methods: This retrospective case series analyzed data from two neonates treated for laryngomalacia at Children Center Hospital Tehran between 2021 and 2022. Inclusion criteria were neonates beyond 28 weeks gestation without congenital abnormalities and with an RDS score ≥8. Exclusion criteria included preterm neonates (<28 weeks), an RDS score <8, and congenital abnormalities. Data collection involved measures such as respiratory assistance, stridor, feeding issues, oxygen requirement, hospital stay duration, ventilation days, gestational age, RDS score, retraction severity, and amniotic blood gas values. Ethical considerations were observed throughout the study. Results: The first neonate, a 29-day-old female with a gestational age of 36 weeks and 5 days, required HFNC and laser ablation, leading to the resolution of stridor and feeding difficulties. Her hospital stay was 46 days. The second neonate, a 16-day-old male born at 38 weeks gestation, experienced complications including VAP and required a more extended treatment course, including intubation, NIV, CPAP, and HFNC, culminating in an 80-day hospital stay. Conclusion: The study highlights the importance of personalized and adaptable treatment strategies in managing laryngomalacia in neonates. The variability in clinical presentations and responses to treatment underscores the need for ongoing research and the development of refined management protocols. A multidisciplinary approach, incorporating timely diagnosis and flexible intervention, is crucial for optimal patient outcomes.